Reconsidering Contact Precautions for Endemic Methicillin-Resistant Staphylococcus aureus and Vancomycin-Resistant Enterococcus. (3rd July 2015) - Morgan, Daniel J.; Murthy, Rekha; Munoz-Price, L. Silvia; Barnden, Marsha; Camins, Bernard C.; Johnston, B. Lynn; Rubin, Zachary; Sullivan, Kaede V.; Shane, Andi L.; Dellinger, E. Patchen; Rupp, Mark E.; Bearman, Gonzalo
Abstract : BACKGROUND: Whether contact precautions (CP) are required to control the endemic transmission of methicillin-resistant Staphylococcus aureus (MRSA) or vancomycin-resistant Enterococcus (VRE) in acute care hospitals is controversial in light of improvements in hand hygiene, MRSA decolonization, environmental cleaning and disinfection, fomite elimination, and chlorhexidine bathing. OBJECTIVE: To provide a framework for decision making around use of CP for endemic MRSA and VRE based on a summary of evidence related to use of CP, including impact on patients and patient care processes, and current practices in use of CP for MRSA and VRE in US hospitals. DESIGN: A literature review, a survey of Society for Healthcare Epidemiology of America Research Network members on use of CP, and a detailed examination of the experience of a convenience sample of hospitals not using CP for MRSA or VRE. PARTICIPANTS: Hospital epidemiologists and infection prevention experts. RESULTS: No high quality data support or reject use of CP for endemic MRSA or VRE. Our survey found more than 90% of responding hospitals currently use CP for MRSA and VRE, but approximately 60% are interested in using CP in a different manner. More than 30 US hospitals do not use CP for control of endemic MRSA or VRE. CONCLUSIONS: Higher quality research on the benefits and harms of CP in the control of endemic MRSA and VRE is needed. Until more definitive data are available, the use of CP for endemic MRSA or VRE in acute care hospitals should be guided by local needs and resources. Infect Control Hosp Epidemiol 2015;36(10):1163–1172